Contribution of IL-17C-mediated macrophage polarization to Type 17 inflammation in neutrophilic asthma - Yuhuan Wen; Qile Chen; Hao Wang; Shiyun Xie; Honglv Chen; Wenruo Yao; Le Zhang; Weimin Sun; Junjie Wen; Xiaojing Yang; Kian Fan Chung; Qingling Zhang; et al. (Cell Communication and Signaling)
Abstract Background IL-17C has been described in a variety of inflammatory diseases driven by neutrophils. However, the role of IL-17C in neutrophilic asthma has not been completely characterized. Methods The level of IL-17C in asthmatic patients and mice was assessed. Il-17c-deficient mice or mice treated with exogenous rmIL-17C were performed for OVA/CFA-induced asthmatic mice model. Pulmonary inflammation was evaluated by histological analysis, flow cytometry and cytokine analysis. Il-17re-overexpressed Raw264.7 were used in vitro to investigate the role of IL-17C in macrophage polarization. Results Here, we show IL-17C were increased in serum or plasma from asthmatic patients and OVA/CFA-induced asthma mice. In the OVA/CFA-induced model, exogenous rmIL-17C aggravated neutrophil- and Type 17-dominated inflammation and promoted M1 macrophage differentiation, whereas deficiency of Il-17c reversed the pro-inflammatory phenotypes and inhibited the expansion of M1 macrophages. In vitro, IL-17C in synergy with IFN-γ induced STAT1 activation in Il-17re overexpressed Raw264.7 to upregulate M1-related genes expression, and promoted pro-inflammatory M1 polymerization, whereas IL-17C in contrast to the effect of IL-4 inhibited STAT6 activation, to reduce Raw264.7 differentiation to M2 macrophage and functional M2-related genes expression. Conclusions IL-17C promotes allergic inflammation via M1 polarization of pulmonary macrophages in neutrophilic asthma. Modulation of the IL-17C/IL-17RE axis represents a novel therapeutic target in neutrophilic asthma.